انعكاسات تقلبات أسواق النفط والغاز الطبيعي بسبب جائحة كوفيد-19 على اقتصاديات الدول العربية المصدرة للنفط والغاز - بن موسى نبيل (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
حاولت الدراسة تسليط الضوء على تطورات أسواق النفط والغاز في العالم خلال جائحة كوفيد-19 وإبراز انعكاساتها على اقتصاديات الدول العربية المصدرة للنفط والغاز في محاولة للمساعدة على تبني سياسات مناسبة للتعامل مع تلك الانعكاسات لتحقيق استدامة النمو والتنمية. خلصت الدراسة إلى أن أسواق النفط والغاز عرفت خلال جائحة كوفيد-19 تقلبات حادة وتاريخية، الأمر الذي صعّب على الدول العربية المصدرة للنفط والغاز التصدي للجائحة، وهو ما ينطوي على تأثيرات سلبية على أمنها الاقتصادي بعد تراجع حصتها السوقية وصعوبة تحقيق أسعار تغطي نفقاتها. Abstract: The present study attempted to shed light on the developments of the oil and gas markets in the world during the Covid-19 pandemic and to highlight their repercussions on the economies of the Arab oil and gas exporting countries in an attempt to help adopt appropriate policies to deal with those Implications for achieving sustainable growth and development. The study concluded that the oil and gas markets experienced sharp and historical fluctuations during the Covid-19 pandemic making it difficult for Arab oil and gas exporting countries to address the pandemic, which has negative effects on its economic security after the decline in their market share and the difficulty of achieving prices that cover its expenses.